FOOD DIVERSIFICATION TO SUPPORT FOOD SCURITY - I Gede Pasek Mangku (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2017)
Rice is the main food for most people of Indonesia. Level of rice consumption in Indonesia reached 139 kg/capita/year. This value is very high when compared to other countries such as Japan 45 kg/capita/year, Malaysia 80 kg/capita/year and Thailand 90 kg/ capita/year. This data shows that Indonesia relies heavily on one of the foodstuffs. To meet the needs of the rice Indonesia to import as much as 24 929 tons of rice (Anon, 2004a; Santosa, 2016). Toreduce dependence of rice and imfort, so that food diversification program by using local food, like cassava is one alternative that can be done. Diversification of staple food have to do with the development and introduction of alternative materials substitute of rice that resembles rice in both form and content of nutrients. Cassava (Manihotesculenta) is a kind of tubers that contain high carbohydrates with low levels of amylose and high amylopectin contents so it can be used as food source of carbohydrates instead of rice (Rismayani, 2007). Diversification of food made people more healty. In addition, diversification is able to create new jobs with the growth of small-midlebusinesswhich process foodstuffs and increasing of agricultural land planted non-rice crops. In an effort to support national food security so diversification program of the utilization of local food as a source of carbohydrate as one of cassava need to be developed. One of the products processed from cassava material that was developed is "analog rice". According to Yuwono, et al., (2013), rice analog is one form of diversification of staple foods prepared from carbohydrate-based raw material with the addition of certain substances to improve the quality of staple foods. Product diversification is expected to support national food security program to reduce rice consumption level without making major changes in people's eating traditions. Keywords: rice, diversification, food security, analog rice